Vertikalna in horizontalna usklajenost pristojnosti sodišč - Knez, Rajko (Podjetje in delo, 2023)
The article analyses the judicial dialogue made possible by the horizontal and vertical interweaving of the jurisdiction of the courts, with the emphasis on former. Two so-called intermediate procedures are highlighted: the request of the courts to assess the constitutionality of general acts before the Constitutional Court and the preliminary ruling procedure before the EU Court of Justice. The focus is also on the roles of both courts in these processes. The courts' dialogue has many advantages, some being emphasised. The article also focuses on the attitude towards the courts being bypassed by the judicial dialogue. This topic is not in the foreground, but is not entirely ignored. The article also separates the latter according to the weight of the legal questions to be answered.The article analyses the judicial dialogue made possible by the horizontal and vertical interweaving of the jurisdiction of the courts, with the emphasis on former. Two so-called intermediate procedures are highlighted: the request of the courts to assess the constitutionality of general acts before the Constitutional Court and the preliminary ruling procedure before the EU Court of Justice. The focus is also on the roles of both courts in these processes. The courts' dialogue has many advantages, some being emphasised. The article also focuses on the attitude towards the courts being bypassed by the judicial dialogue. This topic is not in the foreground, but is not entirely ignored. The article also separates the latter according to the weight of the legal questions to be answered.
Keywords: pravna sredstva; predhodno odločanje; sodišča; Sodišče EU; sodstvo; ustavna pritožba; Ustavno sodišče; ustavnost